The Opacity of the Self, Sovereignty & Freedom: In Conversation with Arendt, Butler & Derrida - Giles, Graham; Delgado Vintimilla, Cristina (Paideusis, 2007)
This paper asks and examines the question “who are you?” In doing so it embarks across the conceptual terrain of subjectivity, passing through five different regions. First is the subject and otherness, in which are considered Arendtian notions of the “who” of the individual in the appearing world. Next is the relation between the “I” and the “you” in systems of recognition, and how those systems are creations and expressions of social normativity. This is followed by the idea of the sovereignty of the self as a reaction to its dislocation within systems of recognition. Sovereignty as such is viewed through the thought of Jacques Derrida and Hannah Arendt. With Foucault, the authors approach the question of social normativity as a frame rather than a constraint by which the self is stylized. The fourth section of the paper then explores self-questioning as a means of explicit or intentional self-stylization. Contrasting the “mere liberation” of thinking in Arendt’s thought with broader understandings of freedom, the fifth section relates Arendt’s conception of the miraculous with Derrida’s of the event. The paper’s trajectory returns in conclusion to the implications of its course for the initial question of who one is, particularly with respect to the teaching subject.